Contusion concomitant with ischemia injury aggravates skeletal muscle necrosis and hinders muscle functional recovery. Issue 17 (September 2022) - Deng, Peijun; Qiu, Shuai; Liao, Fawei; Jiang, Yifei; Zheng, Canbin; Zhu, Qingtang
Contusion concomitant with ischemia injury to skeletal muscles is common in civilian and battlefield trauma. Despite their clinical importance, few experimental studies on these injuries are reported. The present study established a rat skeletal muscle contusion concomitant with ischemia injury model to identify skeletal muscle alterations compared with contusion injury or ischemia injury. Macroscopic and microscopic morphological evaluation showed that contusion concomitant with ischemia injury aggravated muscle edema and hematoxylin–eosin (HE) injury score at 24 h postinjury. Serum creatine kinase (CK) and lactate dehydrogenase (LDH) levels, together with gastrocnemius muscle (GM) tumor necrosis factor-alpha (TNF-α) content elevated at 24 h postinjury too. During the 28-day follow-up, electrophysiological and contractile impairment was more severe in the contusion concomitant with ischemia injury group. In addition, contusion concomitant with ischemia injury decreased the percentage of larger (600–3000 μm 2 ) fibers and increased the fibrotic area and collagen I proportion in the GM. Smaller proportions of Pax7 + and MyoD + satellite cells (SCs) were observed in the contusion concomitant with ischemia injury group at 7 days postinjury. In conclusion, contusion concomitant with ischemia injury to skeletal muscle not only aggravates early muscle fiber necrosis but also hinders muscle functional recovery by impairing SC differentiation and exacerbating fibrosis during skeletal muscle repair.